Understanding paramagnetic spin correlations in the spin-liquid pyrochlore Tb 2 Ti 2 O 7 - Kao, Ying-Jer; Enjalran, Matthew; Maestro, Adrian Del; Molavian, Hamid R.; Gingras, Michel J. P. (Physical Review B, 2003)
Recent elastic and inelastic neutron scattering studies of the highly frustrated pyrochlore antiferromagnet Tb2Ti2O7 have shown some very intriguing features that cannot be modeled by the local 〈111〉 classical Ising model, naively expected to describe this system at low temperatures. By including single-ion excitations from the ground state doublet to higher crystal field levels, we successfully describe the elastic neutron scattering pattern and dispersion relations in Tb2Ti2O7, quantitatively consistent with experimental observations. © 2003 The American Physical Society.
Keywords: article; complex formation; correlation analysis; dept.phy; low temperature; molecular model; neutron scattering; oxygen; quantitative analysis; terbium; titanium